2011
DOI: 10.1093/aob/mcr159
|View full text |Cite
|
Sign up to set email alerts
|

Mating system shifts on the trailing edge

Abstract: Small populations on the trailing edge are especially vulnerable to environmental change because of inadequate levels of cross-fertilization. Evidence is presented that a deficiency of cross-seed production is due to inadequate pollinator services and a paucity of self-incompatibility alleles within populations. Evidence also is presented that if plants are self-compatible, self-fertilization may compensate in part for this deficiency through a stress-induced increase in levels of self-compatibility and stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
107
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(111 citation statements)
references
References 158 publications
(162 reference statements)
3
107
0
1
Order By: Relevance
“…Self-fertility in inhospitable environments also may be increased in some species through a change in flower development, a common change is a reduction of herkogamy (Levin 2012).This finding corroborates a number of studies that showed that variation in herkogamy levels significantly affected autonomous reproduction (Takebayashi and Delph 2000;Herlihy and Eckert 2007;Brys and Jacquemyn 2012).…”
Section: Discussionsupporting
confidence: 85%
“…Self-fertility in inhospitable environments also may be increased in some species through a change in flower development, a common change is a reduction of herkogamy (Levin 2012).This finding corroborates a number of studies that showed that variation in herkogamy levels significantly affected autonomous reproduction (Takebayashi and Delph 2000;Herlihy and Eckert 2007;Brys and Jacquemyn 2012).…”
Section: Discussionsupporting
confidence: 85%
“…It is likely that selection against inbreeding may have played a role in mitigating the deleterious effects of small population sizes and resulted in our detecting significant excesses of homozygotes in only 2 of the 18 populations examined. Nevertheless, our results indicate that mating was restricted within populations, which might have been caused by an increasing selfing rate along ranges of plant species in response to climate change (Levin, 2012).…”
Section: Genetic Diversity Bottlenecks and Inbreedingmentioning
confidence: 72%
“…The newly discovered evidence for an isolated taxon in the Nyingchi region, Nyingchi Platygyria , adds a further support for the emerging hypothesis that self-fertilization promotes persistence of populations despite isolation and environmental challenges [1,2]. …”
Section: Discussionmentioning
confidence: 96%
“…Several recent studies suggested that environmental condition enforced the evolution of self-fertilization in plants, especially as a strategy to adapt to extreme habitats [1] and along the trailing edge [2]. For example, evidence was reported for indirect selection of mating system during the evolution of drought resistance in the angiosperm genus Mimulus evolution [3].…”
Section: Introductionmentioning
confidence: 99%